The Fifth Biennale of Sydney : Private Symbol : Social Metaphor. - Morgan, Stuart; Pohlen, Annelie; Rattcliff, Carter; Fifth Biennale of Sydney, 1984 (Sydney : Biennale of Sydney, 1984)
Allen, Davida ; Armando ; Art & Language ; Atkinson, Terry ; Beban, Breda ; Beuys, Joseph ; Bevan Tony ; Bezor, Annette ; Boisrond, François ; Booth, Peter ; Ciecierski, Tomasz ; Cragg, Tony ; Davila, Juan ; Dias, Antonio ; Diaz, Gonzalo ; Dittborn, Eugenio ; Droese, Felix ; Dumas, Marlene ; Dwurnik, Edward ; Germana, Mimmo ; Gilbert & Gilbert ; etc.
The Fifth Biennale of Sydney Private Symbol : Social Metaphor, 11 April - 17 June 1984, Art Gallery of New South Wales, Art Gallery Road, Sydney ; Ivan Dougherty Gallery, City Art Institute, Cnr Albion Ave & Selwyn Street Paddington ; Aspects of Australian Figurative Painting 1942-1962, S H Ervin Gallery, National Trust, Observatory Hill ; Colin McCahon, Power Gallery of Contemporary Art, University of Sydney ; Biennale Forums, 13-15 April, Merewether Building, University of Sydney, Organised by the Power institute of Fine Arts
English
kunstcatalogus